Characteristics and influencing factors of gut microbiota in population with sleep disorders - Zhang, Chunhong; Sheng, Qinglin; Wang, Yuanqi; Shen, Qi; Zhai, Yifei; Hu, Dawei; Zhang, Nanjia; Wang, Ziyuan; Yin, Xuebin; Li, Dan; Chen, Youtao (Frontiers in Microbiology, 2025)
IntroductionThe integrated analysis of gut and oral microbiota and their metabolites helps elucidate key factors affecting sleep disorders in populations and provides research insights for understanding sleep regulation mechanisms.MethodsBased on a cross-sectional study design, this research combined 16S sequencing and untargeted metabolomics to investigate lifestyle habits and physical conditions of 165 adult male subjects, systematically examining characteristics of gut and oral microbiota and their metabolites.ResultsAnalysis of gut microbiota revealed significantly reduced microbial diversity in the insomnia group, with predominant phyla being Firmicutes, Actinobacteriota, and Bacteroidetes. At the genus level, the abundance of Blautia was significantly elevated. Gut metabolite analysis showed significant enrichment in metabolic pathways such as “phenylalanine, tyrosine, and tryptophan biosynthesis.” Regarding oral microbiota, no significant difference in diversity was observed between sleepless and normal groups. At the genus level, the sleepless group showed significantly decreased abundance of Streptococcus and increased abundance of Veillonella. Metabolite analysis indicated significant correlation between the sleepless group and metabolic pathways such as “pantothenate and CoA biosynthesis.”DiscussionThis study compared differences in gut and oral microbiota and metabolites between sleepless and normal groups, identifying potential biomarkers for insomnia, including gut Blautia, aromatic amino acid metabolites, salivary Streptococcus and Veillonella, and pantothenate-related metabolites. These findings provide important multi-omics data for investigating the pathological mechanisms of insomnia. We have made changes according to the requirements, please adjust according to the standard.